2016
DOI: 10.4103/1735-3327.197041
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of slice thickness effect on visibility of inferior alveolar canal in cone beam computed tomography images

Abstract: Objective:The aim of this study is to evaluate the effect of slice thickness on the visibility of inferior alveolar canal (IAC) in cone-beam computed tomography (CBCT) images.Materials and Methods:CBCT images of thirty patients (15 male and 15 female) with an age range between 40–50 years old were used. Cross-sectional images were obtained with 0.5, 1, and 2 mm slice thickness and 2 mm interval. Two oral radiologists with at least 5 years' of experience observed all of the 90 images and rated the images based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Goodarzipoor and Arzi (2016), in their study, concluded that slice thickness had no effect on IAC visibility in cross-sectional images (16), which was in line with the results of the present study, whose visibility was compared in three thicknesses of 0.5, 1 and 2.…”
Section: Discussionsupporting
confidence: 92%
“…Goodarzipoor and Arzi (2016), in their study, concluded that slice thickness had no effect on IAC visibility in cross-sectional images (16), which was in line with the results of the present study, whose visibility was compared in three thicknesses of 0.5, 1 and 2.…”
Section: Discussionsupporting
confidence: 92%
“…However, several studies demonstrated different conclusions on the dependence of the slice thickness of CBCT scans and the detection of the anatomical and other structures, as well as the way that reduces artefacts [18][19][20][21][22][23][24]. Our choice of slice thickness was 1 mm for good and moderate detection of CS without missing it and with high reduction of artefacts in this case.…”
Section: Discussionmentioning
confidence: 81%
“…A previous study reported that cases of IAN damage were caused more frequently by MTM extraction surgery than by dental implantation or orthognathic surgery [ 10 ]. The spatial relationship between the MTM root and the mandibular canal (MC) is the most significant risk factor for IAN injury [ 11 15 ].…”
Section: Introductionmentioning
confidence: 99%